The view from beneath the ceiling: The link between development and practice for women in midmanagement leadership roles - Carolyn M. Clark; Rosemary S. Caffarella; Peggy B. Ingram (Adult Education Research Conference, 1994)
This study examines the leadership experiences of midmanagement women in light of major themes in the women's developmental literature.